Food Insecurity and Mental Health among Adolescent Girls in Bangladesh: A Mixed-Methods Study of Depression, Anxiety, and Psychosocial Vulnerability - Robin, Saiful Islam; Tanvir, Fakhrul Abedin (International Journal of Health Sciences, 2025)
Purpose: Food insecurity significantly impacts adolescent mental health, particularly in at-risk populations facing poverty and systemic disparities that exacerbate both nutritional insufficiency and psychological stress. This study investigates the correlations between food insecurity and mental health in young girls aged 12 to 18 exhibiting signs of depression, anxiety, and stress. Methodology: A cross-sectional mixed-method study was performed utilizing validated tools (Food Insecurity Experience Scale, PHQ-9, and GAD-7) alongside qualitative narratives from interviews to illustrate lived experiences. The participants consisted of a sample of 350 low-income adolescents from urban and rural areas. Findings: In multivariate analysis, moderate-to-severe food insecurity was independently correlated with heightened probabilities of depression (OR=2.8, p<0.01) and anxiety (OR=2.3, p<0.05). Qualitative themes corroborated these findings, as participants articulated discomfort stemming from inconsistent food access, stigma, and home instability. The research indicates that food insecurity serves as both a physical developmental impediment and a contributor to psychosocial vulnerabilities, hence heightening the risk of persistent mental health disorders over time. Unique Contribution to Theory, Practice and Policy: The implications underscore the significance of the integrated Clinical Care and Friendly Portia Nutrition intervention. The cross-sectional design limits establishing causation, and the sample's representativeness may not extend to broader teenage populations. It is recommended that prospective longitudinal research in diverse settings offer direction for policy and focused treatments.